2022
DOI: 10.1097/md.0000000000028895
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Qinghua Zhixie Decoction against diarrhea-predominate irritable bowel syndrome

Abstract: Background: Diarrhea-predominant irritable bowel syndrome (D-IBS) is the main subtypes of irritable bowel syndrome (IBS). In recent years, more than half of IBS patients have received complementary and alternative medicine. Traditional Chinese herbal formula is widely used in Asia, and clinical studies have also found that Chinese herbal formula could significantly improve abdominal pain and diarrhea. We plan to carry out a randomized, controlled, double blind, clinical studies to observe the clinical efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Traditional Chinese herbal formulas (CHFs), such as "Sijunzi Tang, Tongxieyaofang, Buzhongyiqi Tang, and Shenlingbaizhu Tang", are widely used for chronic diarrhea therapy in Asia, and clinical studies have also found that CHF could significantly improve abdominal pain and diarrhea in D-IBS and functional diarrhea patients (Gou et al, 2016;Jandhyala, 2015;Ji et al, 2022;Zhou et al, 2019). A growing number of studies have supported the view that Chinese herbal formulas alleviate the symptoms of diarrhea by modulating the fecal microbiota because they inevitably interact with the gut microbiota with poor oral bioavailability (Zu et al, 2018) (Jia et al, 2019;Ma et al, 2020;Qu et al, 2021;Shi et al, 2019).…”
Section: Traditional Chinese Herbs Improve Chronic Diarrheamentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional Chinese herbal formulas (CHFs), such as "Sijunzi Tang, Tongxieyaofang, Buzhongyiqi Tang, and Shenlingbaizhu Tang", are widely used for chronic diarrhea therapy in Asia, and clinical studies have also found that CHF could significantly improve abdominal pain and diarrhea in D-IBS and functional diarrhea patients (Gou et al, 2016;Jandhyala, 2015;Ji et al, 2022;Zhou et al, 2019). A growing number of studies have supported the view that Chinese herbal formulas alleviate the symptoms of diarrhea by modulating the fecal microbiota because they inevitably interact with the gut microbiota with poor oral bioavailability (Zu et al, 2018) (Jia et al, 2019;Ma et al, 2020;Qu et al, 2021;Shi et al, 2019).…”
Section: Traditional Chinese Herbs Improve Chronic Diarrheamentioning
confidence: 99%
“…A growing number of studies have supported the view that Chinese herbal formulas alleviate the symptoms of diarrhea by modulating the fecal microbiota because they inevitably interact with the gut microbiota with poor oral bioavailability (Zu et al, 2018 ). Qinghua Zhixie decoction (QZD) consists of Fengfei Cao ( Pteris multifida Poir ), Dijin Cao ( Elsholtzia Ciliata Hyland ), Bugu Zhi ( Psoralea corylifolia ), Huanglian ( Coptis chinensis ), Muxiang ( Radix Aucklandiae ), Paojiang ( Baked ginger ), Baishao ( Radix paeoniae alba ), Fangfeng ( Radix Saposhnikoviae ), Cangzhu ( Rhizoma atractylodis ), Baizhu ( Rhizoma Atractylodis Macrocephalae ), and Xianhe Cao ( Agrimonia pilosa ) and can regulate the gut microbiota and reduce 5‐hydroxytryptamine and vasoactive intestinal polypeptides to improve diarrhea (Ji et al, 2022 ). Gegen Qinlian decoction (GD), as a classic prescription for diarrhea with IDHS, is composed of Pueraria lobata ( Willd .)…”
Section: Intervention Effect Of Chp On Diarrhea By Modulation Of Gut ...mentioning
confidence: 99%
See 1 more Smart Citation